FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA - Septianasari, Frasiska Trie (JURNAL MEDIA KESEHATAN, 2015)
Less of nutrients is one of the nutrient disturbance disease because the less of foodconcumptions. Children’s weights is less to 80% index of weight accoding to age. PuskesmasSukamerindu had the highest score of child under five years old with nutrientless. Thepurpose of this research is to know the relation of mothers knowledge degree economic leveland the sun of family members with nutrient degree at Puskesmas Sukamerindu. This researchuse descriptive analytic research desaign with case control scheme. The population in thisresearch is all of the children under five years old in Puskesmas Sukamerindu region, thesample is 60 childs under five years old with case sample is taking by total sampling andcontrol sample is taking by purposive sampling. The method of taking the data is usingsecondary data and primary data (quisionary whereas the method of analyzing data is usingChi-Square). The result of univaried analyzing is almost half of part (31,7%) mother’s hadless of knowledge degree, almost half of past (45,0%) family had low of economic level,almost half of part (46,7%) family had the sum of family members > 4 persons. The result ofbivaried analyzing shows there is a mean relation between mothers knowledge degree (p =0,000), economic level (p = 0,000) with nutriet degree of child under five years old. The resultof this research shows there isn’t a relation between the sum of family member (p = 0,547)with nutrient degree of child under years old. Hoping for the paramedics especially midwifecan increasing the nutrient knowledge of the mothers with give a conseling about nutrient anddo the monitoring nutrient degree periodicly.